Rwanda Economic Update, January 2022, Edition No. 18 : Boosting Regional Integration in the Post-COVID Era - World Bank (World Bank, Kigali, 2022)
Global economic growth has picked up in 2021 and has now surpassed its pre-pandemic level. The National Bank of Rwanda (NBR) has maintained an accommodative monetary stance and other measures to support the recovery, taking advantage of low inflation. The government’s continued fiscal expansion is also providing support to the economy. Regional integration offers significant benefits for Rwanda, including greater potential for scale economies, opportunities for learning to export and produce higher-quality goods, and cooperation to improve trade facilitation. Regional trade will be enhanced by boosting trade with non- East African Community (EAC) members. The African continental free trade area (AfCFTA) can boost growth and trade integration. The development of Rwanda as a regional logistics hub, serving as an intermediating node between the East and Central Africa regions offers prospects to increase revenues and generate efficiency gains through the concentration of logistics services. The white paper on logistics and distribution services strategy for Rwanda, prepared with the support of the World Bank, laid out a two-phase strategy for the rollout of Rwanda as regional logistic hub. This involved: (i) improving the efficiency of Rwanda’s role as a land-bridge for re-exports to Goma in Democratic Republic of Congo (DRC); and (ii) establishing a regional logistics hub in Rwanda linked to a primary multi-modal hub at Kisangani and a secondary multi-modal hub at Kindu.